2010
DOI: 10.1021/ic100140j
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Phosphorus Guest Ions in the Calcium Silicate Phases of Portland Cement from 31P MAS NMR Spectroscopy

Abstract: Portland cements may contain small quantities of phosphorus (typically below 0.5 wt % P(2)O(5)), originating from either the raw materials or alternative sources of fuel used to heat the cement kilns. This work reports the first (31)P MAS NMR study of anhydrous and hydrated Portland cements that focuses on the phase and site preferences of the (PO(4))(3-) guest ions in the main clinker phases and hydration products. The observed (31)P chemical shifts (10 to -2 ppm), the (31)P chemical shift anisotropy, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Magic angle spinning (MAS) NMR spectroscopy has in particular been widely used to probe local environments of aluminium and silicon nuclei in cements. Nuclei such as 31 P have not been exploited to the same extent in the context of cement chemistry, despite favourable NMR properties; notable investigations appear in the field of biocompatible dental cements [30,31] and the study of Portland cement [32]. For the phosphate-modified CAC systems studied here, 31 P is a key nucleus which has not previously been examined through the use of advanced NMR techniques.…”
Section: Preprint Version Of Accepted Article Please Cite As: Ma Cmentioning
confidence: 99%
“…Magic angle spinning (MAS) NMR spectroscopy has in particular been widely used to probe local environments of aluminium and silicon nuclei in cements. Nuclei such as 31 P have not been exploited to the same extent in the context of cement chemistry, despite favourable NMR properties; notable investigations appear in the field of biocompatible dental cements [30,31] and the study of Portland cement [32]. For the phosphate-modified CAC systems studied here, 31 P is a key nucleus which has not previously been examined through the use of advanced NMR techniques.…”
Section: Preprint Version Of Accepted Article Please Cite As: Ma Cmentioning
confidence: 99%
“…100% natural abundance and high gyromagnetic ratios), which may be present in cementitious systems in small amounts (below 0 . 5 wt% in Portland cement), can be utilised in NMR experiments, as recently demonstrated in studies of fluoride mineralisation of anhydrous Portland cement (Tran et al, 2009) and of the incorporation of phosphorus in the calcium silicate phases of Portland cement (Poulsen et al, 2010). The 29 Si chemical shift reflects primarily the degree of condensation of SiO 4 tetrahedra (Q n , n ¼ 0, 1, 2, 3, 4; Lippmaa et al, 1980), allowing a distinction of the resonances from alite, belite and the C-S-H phase in hydrating Portland cements.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…This assignment was further supported by a determination of the spinlattice relaxation times for 31 P in alite and belite, which exhibit the same ratio as observed for the corresponding 29 Si relaxation times. 242 Donor numbers (DN) of the fluorinated Me Pr carbonate (MPC) derivs were estimated by 29 Si NMR chemical shifts of triphenylsilanol. DN of the fluorinated MPC derivatives except PFPMC tends to decrease with increasing the number of fluorine atom.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%
“…This work reports the first 31 P MAS NMR study of anhydrated and hydrated Portland cements that focuses on the phase and site preferences of the (PO 4 ) 3 À guest ions in the main clinker phases and hydration products. 383 Based on powder X-ray diffraction and 31 P Magic Angle Spinning NMR (MAS NMR) investigations of mixed phosphate Al 0.5 Ga 0.5 PO 4 , prepared by co-precipipitation method followed by annealing at 900 1C for 24 h, it is shown that Al 0.5 Ga 0.5 PO 4 phase crystallises in hexagonal form with lattice parameter a = 0.491(2) and c = 1.106(4) nm. 384 The authors present, for the first time, a systematic and comprehensive study of 31 P NMR chemical shift as a function of 4 experimental parameters: (i) external concentration, (ii) concentration of chelating agent, (iii) pH value of the aqueous component of the solvent system and (iv) temperature of the NMR measurement.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%